Islamization of Science from a Historical-Philosophical Perspective - Mochammad Achwan Baharuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This paper discusses the idea of science which tends to get a negative response and does not develop. In fact, the maingoal is to provide a new awareness in obtaining modern knowledge in accordance with the needs of Muslims. Themain focus of writing is how the nature or purpose of the Islamization of Science. The main focus is discussed witha descriptive qualitative method through a historical-philosophical approach based on literature data. This papershows that the essence of the idea of the Islamization of science is a movement for the renewal of science which basesitself on the fact that modern science is developing contrary to religion, so there is a need for a cleansing liberationmovement. This idea has major implications, namely right and wrong between science and religion. In fact, thestandard of truth is different from one another so that it forces the truth of one (religion) to justify knowledge or viceversa creates an attitude of human disharmony. Therefore, there is a need for a new awareness that respects thedifferences between the two in obtaining new knowledge in order to build a more advanced human civilization.